Risk Assessment in Periodontal Disease – A New Way of Predicting the Periodontal Disease Outcome: Life Sciences -Dentistry - Bhuvaneswarri.MDS, Dr. J.; JuliusAmaldas, Dr.; Ramya.V, Dr. (International Journal of Life Science and Pharma Research, 2023)
The present review aims to assess the clinical significance of the risk assessment tool, in periodontal diagnosis.Periodontal disease is a multi-factorial disease. It has been proven that certain risk factors are associated with diseasedevelopment. In addition, host-microbiome interaction is associated with periodontal disease. So, treating a disease requires adifferent approach. Risk assessment in periodontics estimates the risk of susceptibility to periodontal disease. It consists ofassessing the level of bleeding on probing, pocket depth, tooth loss, radiographic bone loss, loss of attachment, patient age,systemic condition of the patients, and finally, an evaluation of environmental and behavioral factors. All these factors areevaluated together. This helps determine the patient’s risk for periodontal disease and its progression for an individual approach.Evaluating the likelihood of developing periodontal disease can play a vital role in clinical decision-making by providing valuableinformation to design appropriate treatment plans. However, controlling risk factors should become a more explicit focus inmany dental practices. This article reviews the application of risk assessment in clinical setup and periodontal diseasemanagement to the population and groups at risk of developing periodontal disease. This review addresses gaps in previousarticles by comprehensively covering all aspects of periodontal disease. Most of the review studies focus on epidemiology andmanagement of the disease, so by proper awareness about a disease and its management, the burden of the disease and its illeffects can be reduced. Based on the article’s findings, implementing healthy dietary habits, making lifestyle changes, and managingrisk factors can effectively control the increasing incidence of periodontal disease and reduce the likelihood of developing it.